Formulating Business Strategy fo a Social Business Company; Maximizing Maluku's Big Potential of Seaweed - Ganiamalia, Mustika; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2012)
Maluku is one of province in Indonesia which is rich with natural resources, but in the same time Maluku is one of the poorest provinces in Indonesia. One of possible cause is not yet managed natural resources in the Maluku optimally. Maluku Ventura is a social-based company that will manage one of the natural resources that exist in the Maluku professionally. Resource that has great potential in Maluku and will be managed by Maluku Ventura is seaweed.Trading of cottonii dried seaweed in the Maluku began to grow since the last five years. Dried cottonii of Maluku is in great demand because buyers have a relatively better quality than the dry cottonii from other areas, for example from South Sulawesi. Buyers, particularly exporters began looking for a dry cottonii from Maluku because of the larger physical size than dry cottonii from South Sulawesi.This final project aims to analyze the development of business model for Maluku Ventura. And for the next step is preparing business strategy using a diamond model. The methodology used is literature study and survey to collect data.After data is collected, the next step is to make the business model. Business model used in this final project is a model of Hamel. In this model, the business model is divided into four pillars: core strategy, value network, strategic resources and the interface with the target group. Core strategy of the company was started by defining the vision of Maluku Ventura, which to be the biggest and sustainable social company in Maluku to increase Maluku's people quality of life. The core business of this company is raw dried seaweed trading. While for the value network of Maluku Ventura is creating the group in the training season. This group consists of farmers and their families. Training will be held to improve their knowledge. Strategic resources for Maluku Ventura are funding the farmers by cooperation with local banks and also employees with high skills. While the last pillar of the business model is interface with the target group. In this pillar, China is the main target of the Maluku Ventura.After develop the business model, the next step is to formulate a business strategy by using a diamond model. Arena for Maluku Ventura is factories and processors in China. While the vehicles for Maluku Ventura is to do a vertical alliance. For staging and pacing, Maluku planning to do direct trading in 2012, build processors in 2014 and build end user factory in 2017. As differentiators, Maluku Ventura builds brands and do price competition. Economies of scale play an important role in the economic logic stage, through economies of scale, Maluku Ventura can reduce costs. Keywords: business model, business strategy diamond model